Insight into MoS2 Synthesis with Biophotoelectrochemical Engineering and Applications in Levofloxacin Elimination - Zeng, L.; Li, Xinyong; Fan, S.; Zhang, M.; Yin, Z.; Tadé, Moses; Liu, Shaomin (2018)
© Copyright 2018 American Chemical Society. Biosynthesis of nanomaterials is an emerging technology in recent decades ascribed to its unique "greener" route and higher energy efficiency. It is superior to the traditional physicochemical synthesis processes, in which hazardous intermediates or high energy-consumption are often inevitable and remain a significant obstacle. In this work, a coupling system based on a photodriven microbial fuel cell (MFC) was constructed to controllably synthesize different sizes of MoS 2 nanomaterials in situ. By virtue of the MFC producing electricity as a driving force, the MoS 42- ions could be reduced to MoS 2 nanoparticles. Impressively, photoexcited electrons produced from a polydopamine coated " 2 nanotube (PDA/" 2 NT) electrode under visible light irradiation (>420 nm) could also be utilized online to facilitate MoS 2 nanoparticle growth effectively. Interestingly, the MoS 2 material was further cultivated on a PDA/" 2 substrate and then biologically modified MoS 2 /PDA/" 2 electrodes were easily obtained, which exhibited unique hydrophilic behavior (14.74°) and bioelectrocatalytic performance for effectively promoting the complete removal of antibiotics in the MFC and photoelectrocatalytic (PEC) cooperative system. Thus, we believe that such obvious advantages of the constructed photoboosted MFC system could provide an environmentally benign pathway to synthesize nanostructured electrode materials and create new opportunities for diverse pollutant removal in situ.